Lightning Overvoltage and Transient Ground Potential Rise in large PV plants - Grange F.; Journet S.; Dawalibi F.P.; Kadir Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric grounding; Electrolysis; Electromagnetic pulse; Lightning protection; CDEGS; Equipment integrity; Lightning overvoltages; Lightning strikes; Over-voltages; PhotoVoltaic plant; Photovoltaic power plant; Safety integrity; TGPR; Transient ground potential rise; Cost effectiveness